Синтаксическая семантика в свободном субстантивном словосочетании (на материале древнеанглийского языка) - Норушайтене, Валерия (Kalbotyra, 1987)
The article deals with the semantic patterns of free noun combinations and their correspondences on the surface level in terms of syntactic patterns in Old English. The semantics of a noun combination is conditioned by the semantics of the modifier, the form of the leading noun and the syntactic function of the combination in the sentence.